2017
DOI: 10.17509/ijal.v7i2.8127
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Coded and Non-Coded Correction Feedback on the Quality of Indonesian Efl Students’ Writing

Abstract: Written corrective feedback (WCF) in L2 writing classrooms has gained considerable attention in applied linguistics research over the past twenty years. WCF may take different forms of teacher's responses to errors in students' texts, among others Coded-Correction Feedback (CCF) and NonCoded Correction Feedback (NCCF). A number of research studies on the effectiveness of various types of corrective feedback have been undertaken; however the effect of CCF and NCCF on the quality of students' writing in Indonesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The findings showed that most of the first grade students managed to correct their errors after receiving direct corrective feedback. Saukah et al (2017) conducted research to investigate the effects of Coded Correction Feedback (CCF) and Non-coded Correction Feedback (NCCF) on senior high school students' writing quality. The findings of the study revealed that students' writing improved more with CCF than with NCCF because CCF promotes awareness with noticing as well as understanding.…”
Section: Discussionmentioning
confidence: 99%
“…The findings showed that most of the first grade students managed to correct their errors after receiving direct corrective feedback. Saukah et al (2017) conducted research to investigate the effects of Coded Correction Feedback (CCF) and Non-coded Correction Feedback (NCCF) on senior high school students' writing quality. The findings of the study revealed that students' writing improved more with CCF than with NCCF because CCF promotes awareness with noticing as well as understanding.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to indirect feedback, we can have two subtypes: coded and un-coded feedback. Research regarding this topic has demonstrated that indirect coded feedback could be more effective than indirect un-coded feedback (e.g., Salimi & Valizadeh, 2015;Saukah et al, 2017).…”
Section: Feedback On L2 Writingmentioning
confidence: 99%
“…Previous studies have shown the efficacy of different forms of feedback (e.g., Mirzaii & Aliabadi, 2013;Saukah et al, 2017;Deng et al, 2022;Tan & Manochphinyo, 2017;Yang et al, 2006). Other studies, however, have questioned the effects of feedback over time (e.g., Truscott & Hsu, 2008;Karim & Nassaji, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Their work's relevance to FWCF in that students tend to being attentive to feedback on their composition and understand the justification for their errors when intensive feedback is provided on only certain area of errors. However, FWCF exploration in Indonesian instructional context is somewhat limited (see Kisnanto, 2016;Saukah, Dewanti, & Laksmi, 2017) since the corrective feedback tends to explore more on students' oral competence or oral and grammar (Liskinasih, 2016).…”
Section: Introductionmentioning
confidence: 99%